Halal Tourism in Central Aceh: Investigating How Influencer Trust and Perception of Authenticity Shape Tourist Loyalty - Putra, Ali Syah; Alimin, Erina; Nasib, Nasib; Hou, Amin; Salqaura, Siti Alhamra; Saputra, Jumadil (Jurnal Manajemen Bisnis, 2025)
Research Aims: This research investigates the influence of trust in social media influencers and perceived authenticity on Muslim tourist loyalty at Laut Tawar Lake, Central Aceh. Specifically, it explores how halal tourism perceptions mediate these relationships. This study expands the current understanding of the interplay between influencer trust, authenticity perception, and halal tourism principles in fostering tourist loyalty, while addressing a gap in tourism literature on sharia-compliant destinations.Design/Methodology/Approach: A quantitative approach was employed, with data collected from 210 Muslim visitors to Danau Laut Tawar using structured questionnaires. The relationships among variables were examined using Partial Least Squares-Structural Equation Modeling (PLS-SEM).Research Findings: The results indicate that influencer trust significantly influences perceptions of halal tourism, thereby positively affecting tourist loyalty. In contrast, perceived authenticity does not significantly affect loyalty. Halal tourism also mediates the relationship between authenticity and tourist loyalty, but not between influencer trust and loyalty.Theoretical Contribution/Originality: This study enriches the halal tourism literature by clarifying the roles of influencer trust and authenticity in shaping Muslim tourist behavior. It offers insights into how perceived halal tourism mediates the connection between trust, authenticity, and loyalty.Practical Implications: The findings emphasize the importance of enhancing halal tourism services, partnering with credible influencers, and promoting authentic cultural experiences to strengthen Muslim tourist engagement. The study provides practical strategies for sharia-compliant tourism marketing and management.Research Limitations/Implications: As this study focuses only on Muslim tourists at Lake Laut Tawar, its findings may not be generalizable to other halal tourism destinations with distinct cultural or regulatory settings.